A NEW FOUR-PARAMETER WEIBULL DISTRIBUTION WITH APPLICATION TO FAILURE TIME DATA - Mohammed, Aminu Suleiman; Ugwuowo, Fidelis Ifeanyi (FUDMA JOURNAL OF SCIENCES, 2020)
A lifetime model called Transmuted Exponential-Weibull Distribution was proposed in this research. Several statistical properties were derived and presented in an explicit form. Maximum likelihood technique is employed for the estimation of model parameters, and a simulation study was performed to examine the behavior of various estimates under different sample sizes and initial parameter values. Through using real-life datasets, it was empirically shown that the new model provides sufficient fits relative to other existing models.
Keywords: Weibull distribution, Reliability function, Maximum Likelihood, Order statistics.